Analysis of Professors' Beliefs about Government Training in the Department of Cauca, Colombia - Chamorro Burgos, Diego Fernando (2023)
This paper intends to analyze, from an exploratory quantitative study, the beliefs about the continuous training that professors of Cauca, Colombia, have received from the national government. Therefore, the investigator designed a questionnaire with fourteen items to which the Expert Judgment technique and Cronbach's Alpha Internal Consistency Test were applied with a result of 0.91, which is considered excellent. Moreover, 310 individuals filled out the questionnaire and the results showed that 33% of professors are convinced of the benefits of training, mainly related to the inclusion of ICT, the development of teaching skills, and educational practice. Likewise, 50% stated that they agree with the benefits of training for teacher improvement, but with some disagreement in school management factors. Meanwhile, 17% declared that they are not convinced of the benefits of training. especially, with the promotion of educational research, the updating of institutional references, the endowment, and the follow-up of the training processes. Therefore, the researcher concludes that, for most professors, the training is acceptable, being satisfied with it. Finally, as a recommendation, the educational community should carry out research that complements, from other paradigms, the results obtained in this work.